EFEKTIVITAS KARTU KATA DALAM PENGAJARAN MENULIS BAHASA JERMAN MELALUI PUISI DI KELAS XI SMAN 2 PURWOREJO - Faridha Nur Rahany, Dwi Rahayu P. R., Nur Fitri S., dan Budi Santoso (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
This research aims to know the effectiveness of word card in teaching writing ofGerman language through poetry as the teaching material in class XI SMAN 2Purworejo.This is a quasi-experiment research using group control design, pre-test and posttestdesign. The sample of this research was taken from Class XI IPA 1 as an experimentclass and Class XI IPS 3 as a control class. This research employed random-samplingtechnique. The data collection was taken based on the result of pre-test and post-test.The technique of data analysis used t-test toward the final-test score between theexperiment and control class.The result reveals that t = 2,037 with sig = 0,045 á = 0,05, thus it can beconcluded that (1) there is an ability difference of the students class XI SMA N 2Purworejo, between the class taught using word card and the class taught not usingword card, 2) the writing ability of the students taught using word card is better thanthose who are not.. The more vocabulary the students master the better their writingability is. This method is a teaching way and an effective introduction toward GermanLiterature in senior high school.Key words: word card, teaching writing, German poetry